2019
DOI: 10.1186/s12884-019-2540-z
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of prenatal care use and HIV testing during pregnancy: a population-based, cross-sectional study of 7080 women of reproductive age in Mozambique

Abstract: Background:In low-income countries with poor coverage of healthcare services such as Mozambique, antenatal care serves as a vital tool for providing life-saving and cost-effective services for pregnant mothers. Nonetheless, many countries in Africa, including Mozambique, are struggling to attain an optimum level of antenatal care (at least 4 visits) utilisation among pregnant women. In the present study, we aimed to assess the sociodemographic and economic factors associated with antenatal care use in Mozambiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Given the importance of HIV testing among women, studies identifying its determinants have been carried out before. These determinants can be classified into socio-demographic determinants (e.g., age, educational attainment, address, religion, marital status, socio-economic status, employment, media exposure, and number of children) or HIV-related determinants (e.g., sexual behaviors, knowledge on HIV, perceptions on HIV testing, consumption of intoxicants, and having talked to mother or female guardian about HIV) [16][17][18][19][20][21]. Other determinants of HIV testing include having a dysfunctional relationship with their spouse/partner, tolerance of domestic violence, experiencing stigma, media exposure, number of lifetime sexual partners, having talked to mother/female guardian regarding HIV testing, ever pregnant, and exposure to public health interventions regarding HIV [16,17,22].…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of HIV testing among women, studies identifying its determinants have been carried out before. These determinants can be classified into socio-demographic determinants (e.g., age, educational attainment, address, religion, marital status, socio-economic status, employment, media exposure, and number of children) or HIV-related determinants (e.g., sexual behaviors, knowledge on HIV, perceptions on HIV testing, consumption of intoxicants, and having talked to mother or female guardian about HIV) [16][17][18][19][20][21]. Other determinants of HIV testing include having a dysfunctional relationship with their spouse/partner, tolerance of domestic violence, experiencing stigma, media exposure, number of lifetime sexual partners, having talked to mother/female guardian regarding HIV testing, ever pregnant, and exposure to public health interventions regarding HIV [16,17,22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DHS used multistage probabilistic sampling methodology to select clusters and households from geographic-based sampling frames that cover the entire territory of participating countries, a design that translates into naturally occurring population hierarchies. However, this study was based on self-reported data which is subject to recall bias and social desirability [51, 52]; for example, there might be errors in reporting respondents’ age at marriage due to the fact that registration of age system is not documented. In addition, the variable for pregnancy termination did not differentiate between miscarriages and abortion and thus blur the true association that exists between the forms of pregnancy termination and child marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the study was based on secondary data from a cross sectional survey. Hence, it cannot be used to infer causality but only to show association between variables [64, 65]. Secondly, the data was collected three years ago, and although the disparity in taking IPTp-SP drugs and TT immunization still exists, the underlying causes may have changed.…”
Section: Discussionmentioning
confidence: 99%